Seed mass, germination and seedling traits for some central Argentinian cacti - Sosa Pivatto, María Susana (2014)
Seed size is one of the most important traits in the regenerative phase of a plant´s life cycle; however, for cactus species the relationship of seed size and germination characteristics and seedling traits is still unclear. We studied the relationship between seed mass and germination and seedling characteristics in 17 cactus species from central Argentina, belonging to different genera and life forms. We measured seed mass, total seed germination, light requirements for germination and mean time to germination for these 17 cacti species; in addition, we recorded seedling size and shape in 15 species. To test light requirements we performed germination experiments under laboratory conditions at 25/15°C (day/night temperatures) and under light or dark conditions. We also calculated seedling volume by measuring seedling height and width. A shape index was obtained by dividing height by width (a value of 1 indicates ?globose? seedlings, whereas, as this value increases, seedlings become ?columnar?). We found no significant relationship between seed mass and any of the germination characteristics considered. However, species with heavier seeds produced bigger seedlings, which were more cylindrical. Adult growth was not totally determined by seedling ?growth form?, because some species that had globose seedlings were columnar at the adult stage.